Suporte social à mulheres vivendo com hiv: repercussões no período gravídico puerperal - Quadros, Jacqueline Silveira de (2017)
From the HIV infection pregnant women and puerperas need specialized clinical follow-up, besides paying attention to their demands in the social dimension. The latter can be evaluated by the set of socio-environmental elements that act in a protective way, enabling individuals to deal adequately with everyday situations, such as care for the maintenance of prophylaxis of vertical HIV transmission. The objective was to evaluate if the social support perceived by pregnant women is different from that perceived by puerperal women living with HIV. This is a cross-sectional quantitative approach. The data collection site was Hospital Universitário de Santa Maria / RS, from April to November 2014, based on an instrument composed of a socio-demographic, clinical and obstetric characterization of pregnant women and puerperal women living with HIV; Social Support Scale for People Living with HIV / AIDS. The eligible population totaled 78 participants. The normality of the variables was evaluated through the Shapiro-wilk test; Descriptive statistics were used to present the baseline characteristics and the T test of independent samples. The Fischer's exact test, the linear logistic regression, was used to obtain estimates of OR and their respective confidence intervals (95% CI) for the intervening factors using the backward method. In all analyzes, significance level was set at p <0.05 and the statistical package SPSS version 21.0 was used. The population of pregnant women was 33.3% (n = 28) and 66.7% (n = 50) were puerperal. When the distribution between the pregnant and postpartum groups was evaluated, it was possible to verify that gestation is a protective factor when compared to the puerperium, since the puerperal women present a 8.8-fold chance of having low social support (OR: 8.80 ; CI: 1.01 - 16.76) and 6.0 times (OR: 6.00; CI: 1.53 - 10.48) for instrumental social support. Participants who are in the gestational period have a greater chance of presenting higher values of total and instrumental social support. In order to verify the reasons for the difference in total and instrumental social support, the characteristics of the groups were evaluated, a significant difference was observed in relation to the ingestion of alcoholic beverages (p = 0.007), use of ART before pregnancy was discovered (p = 0.044) (P = 0.050), support received from friends in emotional social support (p = 0.009), support received from friends in instrumental social support (p = 0.004). It is concluded that it is fundamental that the health professional knows and interacts with the social support network of these women, with the intention of implementing actions that allow them to overcome obstacles in maternal and child health care, especially during this period of family reorganization.